The Effect of Problem Based Learning Model on Critical Thinking Skills of High School Students on Physics Concepts - Fajarna, Rifa Putri; Susanna; Hamid, Abdul; Saminan; Farhan, Ahmad; Nurulwati (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
The persistent inadequacy of students’ critical thinking skills in physics education remains a significant concern within the learning process. This issue is largely attributed to the limited exposure to analytical problem-solving tasks, the monotonous implementation of instructional strategies, and the minimal integration of interactive learning media. Furthermore, the tendency of students to engage in rote memorization of formulas without a thorough conceptual understanding contributes to their weak analytical and problem-solving capacities. This study aims to examine the effectiveness of the Problem-Based Learning (PBL) modeI in enhancing the critical thinking skills of 11th-grade students at SMA Negeri 5 Banda Aceh, particularly in learning Archimedes’ Principle. A quasi-experimental approach was employed using a pretest-posttest control group design, with non-random assignment of participants. The findings demonstrated that the experimental group, which received PBL treatment, attained a higher average post-test score (M = 70.3, SD = 10.93) compared to the control group (M = 63.5, SD = 12.78). Statistical analysis using an independent t-test indicated a significant difference between the groups. Moreover, the normalized gain (N-gain) results showed a moderate level of improvement in the experimental class (0.50) versus a lower level in the control class (0.40). These results suggest that the PBL is more effective in fostering students’ critical thinking than the discovery learning approach.